Uric Acid Potential Role in Systemic Inflammation and Negative Symptoms After Acute Antipsychotic Treatment in Schizophrenia - Borovcanin, Milica M.; Janicijevic, Slavica Minic; Mijailovic, Natasa R.; Jovanovic, Ivan P.; Arsenijevic, Nebojsa N.; Vesic, Katarina (Frontiers in Psychiatry, 2022)
Uric acid (UA) has been shown to have neuroprotective or neurotoxic properties, in relation to specific tissues and diseases that have been studied. Previous studies provided contradictory results on the role of UA in schizophrenia as a neurodegenerative disorder. The aim of this brief report was an additional analysis of UA sera levels in different phases of schizophrenia. Here, 86 patients with first-episode psychosis (FEP) vs. 45 patients with schizophrenia in relapse (SC in relapse) vs. 35 healthy control subjects (HC) were studied before and 1 month after antipsychotic therapy. Further, we aimed to explore the possible correlation of UA with scores presenting clinical features and with serum concentrations of the proinflammatory cytokines interleukin (IL)-6 and IL-17. When comparing the data between all three groups, we did not find significant differences in UA levels, either before or after the applied therapy. Also, comparing sera concentrations of UA in every single group, the analysis did not reveal statistically significant differences between FEP patients, but statistically, a significant difference was found in SC in relapse before and after treatment (334.71 ± 116.84 vs. 289.37 ± 109.15 μmol/L, p = 0.05). Uric acid serum levels correlated with negative sub-score (p = 0.001, r = 0.306), general sub-score (p = 0.015, r = 0.236), and total PANSS score (p = 0.009, r = 0.3) after 1 month of therapy. We have established a statistically significant positive correlation between serum concentrations of UA and IL-6 in exacerbation (p = 0.01, r = 0.220) and with IL-17 after treatment and in the stabilization of psychosis (p = 0.01, r = 0.34), suggesting potential cascades in different phases of schizophrenia that potentiate inflammation.